Gemcitabine: immunomodulatory or immunosuppressive role in the tumor microenvironment - Nemati, Mahnaz; Hsu, Chou-Yi; Nathiya, Deepak; Kumar, M. Ravi; Oghenemaro, Enwa Felix; Kariem, Muthena; Kaur, Parjinder; Bhanot, Deepak; Hjazi, Ahmed; Azam Saedi, Tayebeh (Frontiers in Immunology, 2025)
Gemcitabine (GEM), a nucleoside analog chemotherapy agent, has been widely used in the treatment of various cancers. In recent years, there has been growing interest in understanding the immunomodulatory or immunosuppressive effects of GEM. The immunomodulatory roles of GEM could influence the anti-tumor immune responses via several mechanisms, such as modulation of antigen presentation, cytokine production, and immune cell population. Furthermore, there is evidence that GEM enhances the therapeutic efficacy of immunotherapies, including oncolytic viruses, immune checkpoint inhibitors, CAR T-cells, and therapeutic vaccines. On the other hand, accumulating evidence also proposed that GEM may act as an immunosuppressive agent within the tumor microenvironment, resulting in immune evasion of tumor cells and tumor growth. These paradoxical roles of GEM in modifying immune responses highlight the complexity of GEM interaction with immune cells and responses within the tumor microenvironment. This review aims to provide an overview of the immunomodulatory and immunosuppressive effects of GEM within the tumor microenvironment and how GEM affects the efficacy of cancer immunotherapy.